Preparation of biodegradable functionalized polyesters aimed to be used as surgical adhesives. (August 2019) - Cernadas, T.M.; Gonçalves, F.A.M.M.; Alves, P.; Miguel, S.P.; Cabral, C.; Correia, I.J.; Ferreira, P.
Graphical abstract: Highlights: Biodegradable bioadhesives were usefully obtained for surgical adhesives. Photocrosslinkable biodegradable unsaturated polyesters-based copolymers synthesis. The adhesives presented a strong hydrophilic character and high gel contents. Cell viability was not affected during 7 days in contact with human fibroblast. Abstract: The study and development of new biocompatible materials to be applied as UV-curable adhesives is extremely important to grant the preparation of matrices with suitable mechanical, biological and thermal properties with a fast curing rate. Herein, photocrosslinkable biodegradable copolymers composed of unsaturated polyesters (UP) and lactic acid oligomers functionalized with 2-isocyanatoethyl methacrylate (IEMA) were produced. Henceforth, three different stoichiometric proportions were tested, which, after the addition of a biocompatible photoinitiator (Irgacure® 2959), resulted in flexible, resistant and uniform matrices after 2 min and 30 s of crosslinking. The synthesized materials were then further characterized in terms of chemical composition and thermal/mechanical behavior. The gel content, dynamic contact angles, water sorption capacity and hydrolytic degradation were also assessed. The biocompatibility and antibacterial activity of the produced materials was also evaluated. Taking into account all the data obtained, it may be concluded that the new synthesized biodegradable bioadhesives present promising properties to be used as surgical adhesives.